2020
DOI: 10.21123/bsj.2020.17.1(suppl.).0385
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Method of Linguistic and Statistical Features for Arabic Sentiment Analysis

Abstract: Sentiment analysis refers to the task of identifying polarity of positive and negative for particular text that yield an opinion. Arabic language has been expanded dramatically in the last decade especially with the emergence of social websites (e.g. Twitter, Facebook, etc.). Several studies addressed sentiment analysis for Arabic language using various techniques. The most efficient techniques according to the literature were the machine learning due to their capabilities to build a training model. Yet, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Twitter has received attention from researchers, as in [16,17]. Some of the research on ASA is dedicated to analysing opinions in social media (Facebook, Twitter, YouTube), as in [17][18][19][20][21]. Many available datasets for testing proposed methods of ASA for standard Arabic can be found in [19,20,22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Twitter has received attention from researchers, as in [16,17]. Some of the research on ASA is dedicated to analysing opinions in social media (Facebook, Twitter, YouTube), as in [17][18][19][20][21]. Many available datasets for testing proposed methods of ASA for standard Arabic can be found in [19,20,22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that k-means clustering achieved the best accuracy. The author in [39] suggested combining linguistic and statistical features and sentiment classification using a tweets dataset in Arabic. They used three classifiers: SVM, KNN and ME.…”
Section: Reviews Arabic Language Sentiment Classificationmentioning
confidence: 99%
“…a) Fifth phase: Hybrid supervised classification approach phase: This phase performs two subsections: the first issue is applying ML approach which performs five selected ML classifiers which utilized extensively for ASA: Logistic Regression (LR) [25] [26] [27] [28], Naïve Bayes (NB) [29] [30] [31] [32], K-Nearest Neighbors (KNN) [33] [34] [31] [35], Random Forest (RF) [36] [37] [38] and SVM [33] [39] [40] in addition applying DL approach which performs DL classifier Multi-Layer Perceptron Neural Network (MLP-NN) which applied in [36] [37] for ASA.…”
Section: ) Stop Word Removalmentioning
confidence: 99%